Rhodium‐ and Platinum‐Catalyzed [4+3] Cycloaddition with Concomitant Indole Annulation: Synthesis of Cyclohepta[b]indoles1. Issue 11 (10th February 2013) - Shu, Dongxu; Song, Wangze; Li, Xiaoxun; Tang, Weiping
<x xml:space="preserve">Abstract</x> Various substituted cyclohepta[b]indoles were prepared from propargylic ethers and dienes by a tandem indole annulation/[4+3] cycloaddition (see scheme; Boc=tert‐butoxycarbonyl). Both acyclic and cyclic dienes participated in the [4+3] cycloaddition to afford tri‐ and tetracyclic products, respectively. Electron‐deficient phosphine or phosphite ligands facilitated the tandem reaction.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>